Surface-modified spherical activated carbon for high carbon loading and its desalting performance in flow-electrode capacitive deionization. Issue 74 (22nd July 2016) - Park, Hong-ran; Choi, Jiyeon; Yang, Seungcheol; Kwak, Sung Jo; Jeon, Sung-il; Han, Moon Hee; Kim, Dong Kook
Abstract : We fabricated surface modified activated carbons covered with ion-selective polymer. These materials can be used as powerful dispersants and flow electrodes, and improved desalting efficiency by high carbon loading via electrostatic repulsion. Abstract : We have synthesized a new type of activated carbon (AC) containing ion-selective functional groups, trimethylammonium (AC-N) for anodes and sulfonate (AC-S) for cathodes, for high carbon loading of flow-electrodes. The AC-N and AC-S were partially covered with a 50 nm-thick polymer layer and their surfaces became more hydrophilic than that of bare AC. In the case of bare AC, the maximum carbon concentration in the flow electrodes was 10%, while in the case of the surface-modified AC (AC-N and AC-S), it increased to a maximum of 35% and decreased the viscosity due to the electrostatic repulsion. Moreover, with the increase in carbon concentration, the salt removal efficiencies were improved from 8.2% to 27.7%. This increase in efficiency was attributed to the formation of percolating networks, which occurred because of high carbon loading. The resulting improvement in electronic conductivity at higher loading led to a higher current, and thus an improved salt removal efficiency. Therefore, we expect that the surface-modified AC electrode can be used as a dispersant for hydrophobic AC particles in aqueous solution, as well as in flow electrodes to improve desalting performance in FCDI systems.